Local uniform mesh refinement with moving grids - Gropp, William 1955- (1984)
Local Uniform Mesh Refinement (LUMR) is a powerful technique for solving hyperbolic partial differential equations. However, many problems contain regions where numerical dispersion is very large, such as step fronts. In these regions, mesh refinement is not very efficient. A better approach in these regions is to locally transform the coordinate system to move with the front. This document shows how to combine these two approaches in a way which maintains the advantages of LUMR and the effectiveness of moving grids. Experiments with 2-D scalar problems are presented. (Author).
Keywords: LUMR(Local Uniform Mesh Refinement); Algorithms; Differential equations; Errors; Grids(coordinates); Mesh; Numerical methods and procedures; Scaling factor; Solutions(general); Theoretical Mathematics; Truncation; Two dimensional